A Case Report on Primary Adenocarcinoma of Jejunum - Bhardwar, Vaneeta; Batra, Neha; Goyal, Subhash; Masih, Kanwal (New Frontiers in Medicine and Medical Research Vol. 10, 2021)
Malignancy of small intestine is a very rare entity. Duodenum is the most common site for intestinal malignancy. The lesions present with stricture mostly. Most common cause of small intestine stricture in India is tubercular pathology. Tumors make up a very small percentage of causes of small intestinal obstruction.Small intestinal strictures distal to the duodenum are relatively inaccessible by endoscopy. This leads to difficulty in definitive preoperative diagnosis. The symptoms in case of jejunal malignancy are very nonspecific and a high index of suspicion is required for diagnosis. The objective of this case report is to highlight a case of Primary adenocarcinoma in Jejunum with good outcome after surgical resection.